Substantiation of the technology for reducing dilution by changing the direction of water flow in the dredge section - Kislyakov, Victor E; Zubov, Pavel A; Kokorev, Alexander S (Journal of Degraded and Mining Lands Management, 2024)
The global demand for gold was considered, as well as the ratio of placer gold to ore. It is revealed that there is an increase in the cost of gold mining. This is due to the fact that deposits with simple mining and geological conditions are currently depleted. The dredge method of developing placer deposits is considered. To reduce the cost, the problem of diluting the tailings of ephel dumps was considered. As a solution, a technology for reducing dilution by changing the direction of water flow is proposed. Modeling was carried out and patterns were identified between variables affecting the technological process. This technology can significantly reduce water turbidity, which has a positive effect on the environmental situation in the dredging area. The justification of the technology is given. Also, to justify the effectiveness of the proposed technology, a calculation example is considered. The given example allows us to identify water contamination under various technology options.